Discussion of Income Tax Implications of Various Methods of Accounting for Changing Prices - Basu, Joe (Journal of Accounting Research, 1978)
Joe Basu, Discussion of Income Tax Implications of Various Methods of Accounting for Changing Prices, Journal of Accounting Research, Vol. 16, Studies on Changes in General and Specific Prices: Empirical Research and Public Policy Issues (1978), pp. 234-246